Islamic Banking Existence and Domestic Credit: Study at Seven Countries - Yuafi, Hamdan; Bawono, Anton (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
This paper empirically investigates the determinants of domestic credit across a wide range of 7 countries; these are United Kingdom, Malaysia, Egypt, Kuwait, Qatar, Bahrain and Indonesia. We use dynamic panel estimation to examine effects of exchange rate, inflation, lending interest rate, banking crisis and existence of wholesale Islamic banking on domestic credit. We obtain several notable empirical results. First, the lending interest rate, banking crisis negatively and insignificantly contribute to domestic credit. The existence of Islamic bank has positive and insignificant contribution to domestic credit, while exchange rate positively and significantly contributes to domestic credit.  Inflation negatively and significantly contributes to domestic credit. Second, banking crisis and existence of wholesale Islamic banking show insignificant effect on domestic credit. Third, we find that today’s domestic credit is depended on domestic credit in the previous year.DOI: 10.15408/aiq9i2.4906